FEATURES OF THE LUBRICATION PROCESS IN CONDITIONS OF LIMITING LUBRICATION UNDER LINEAR CONTACT - Dmytrychenko M. F.; Kosenko M. I. (World Science, 2022)
Roller friction bearings are widely used in machine-building, they are one of the most loaded parts. Studying their wear resistance allows to optimize the process of their exploitation, which increases the reliability of mechanisms in general. The purpose of the study is to determine the effect of load on the slip in real bearings of rolling friction. Materials and methods of research: to study the mechanism of slipping, we used the model in the form of a linear contact of two disks, pressed against each other by tangent arcs on the basis of friction machine MI1-M. On the basis of the performed tests it was established that the studied lubricants in the friction pairs of the roller - roller type, when changing the load from 200 to 300 N, reduce the slip factor by 3 - 4%.